Osiowo-Symetryczny Stan Pokrytyczny Płyt Pierścieniowych o Brzegach Swobodnych w Stacjonarnym Polu Temperatur - Mickiewicz, C. (Engineering Transactions, 1967)
The aim of this paper is to find a solution of the problem of post-critical state of a thin annular plate with free edges subject to the action of a stationary temperature field described in an approximate manner by the power function[…].The problem thus formulated arises, for instance, if a ring plate is uniformly heated on the inner edge under conditions of heat exchange with the ambient medium over the lateral surfaces.The state of stress and strain under thermal buckling is considered for such a plate. The problem is solved in an approximate manner. In the first stage the deflections of the plate assuming a membrane state (zero rigidity for bending D = 0) are determined. Next, the influence of the finite rigidity of the plate is taken into account on the basis of the nonlinear Kármán equations for large deflection. The results of the paper have been verified experimentally by model tests. A numerical example agreement of theoretical is given for the values of the parameters obtained from the experiment. The agreement of theoretical and experimental results is found to be satisfactory.